Efektivitas Penggunaan Metode Iqra’ Untuk Meningkatkan Kemampuan Membaca Al-Qur’an Bagi Siswa Muallaf - M. Fazil (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2020)
This study examines the effectiveness of using the iqra' method to improve the ability to read the Qur'an to convert students at Assalam Islamic Solidarity School in Jantho City. Based on the facts in the field, the convert students who are already young have not been able to read the Qur'an well. This institution seeks to improve the quality of convert students in the Qur'an reading, which aims to be one of the motivations for other students to study the Qur'an well. This research has two objectives, namely: How is the ability to read the Qur’an, and the use of the iqra' method to convert students at Assalam Islamic Solidarity School in Jantho City. This research uses a descriptive qualitative approach. Respondents in this study were teachers and students. Data collection techniques in this study are using observation and interviews. From the results of the study found by researchers that the use of iqra' method has been effective against the ability to read for convert students, although there are difficulties in the learning process, caused by lughat (pronunciation) their tongues are still stiff. From this study it can be concluded that every educational institution that is specifically in charge of the education of the Qur'an must be able to improve its quality in carrying out the Qur'anic learning process especially in terms of reading the letters, so that every student, especially converts, can learn the Qur'an 's well and correctly so that they can instill Islamic laws based on the Qur'an and as-Sunnah.